Fossil insect and vertebrate data from Old Crow Flats, northern Yukon, 2007-2009 - Nagwan, Lance; Duane Froese, Department Of Earth; Grant Zazula, Yukon Palaeontologist; Svetlana Kuzmina, Department Of Earth (Canadian Cryospheric Information Network, 2016)
Stratigraphic sections along the Old Crow River, including sites CRH 11 and 12 were studied in the summers of 2007 and 2008. Bulk sampling of stratigraphic intervals associated with the last interglacial was completed for fossil insect studies, and the penultimate interglacial for vertebrate remains. : Purpose: To study paleoenvironments of the last interglacial in the Old Crow Flats, northern Yukon. : Summary: Sediments from river bluff exposures were screened to concentrate remains of small mammals and fossil insects from times in the past that were as warm as or warmer than today.